The Effect of Absorber Stoichiometry on the Stability of Widegap (Ag, Cu)(In, Ga)Se2 Solar Cells. Issue 11 (29th August 2022) - Pearson, Patrick; Keller, Jan; Stolt, Lars; Edoff, Marika; Platzer Björkman, Charlotte
Abstract : (Ag, Cu)(In, Ga)Se2 solar cells with bandgaps of ≈1.45 eV with a large spread in absorber stoichiometry are characterized with the intention of assessing the effect of composition on the stability of the devices. This material is observed to have a poor diffusion length, leading to very strong dependence upon the depletion region width for charge carrier collection. The depletion width is observed to depend strongly upon the stoichiometry value and shrinks significantly after an initial period of dark storage. It is also seen that the depletion width can be varied strongly through light‐soaking and dry‐heat treatments, with prolonged annealing leading to detrimental contraction and light soaking leading to expansion which increases current collection. The extent of depletion width variation in response to the treatments is also clearly linked to absorber stoichiometry. Consequently, the device performance, particularly the current output, exhibits a stoichiometry dependence and is considerably affected after each round of treatment. Possible causes of this behavior are discussed. Abstract : Wide‐gap (Ag, Cu)(In, Ga)Se2 solar cells are characterized after storage, dry annealing, and light‐soaking treatments. Through variation of the depletion width, these treatments induce highly significant changes in the performance of the cells. The absorber stoichiometry is revealed to play an important role, with moderately off‐stoichiometric cells exhibiting large changes in short‐circuit current and close‐stoichiometric cells suffering from open‐circuit voltage losses.